Fabry disease and nursing: Review integrative (Research, Society and Development, 2020)
The objective of this work was to demonstrate the types of treatment and nursing intervention for Fabry's Disease through studies already carried out and published in the literature. It is an integrative review, of a qualitative nature, which used articles available in the Virtual Health Library, specifically in the databases of Latin American and Caribbean Literature in Health Sciences and Medical Literature Analysis and Retrieval System Online, in the period from May 2016 to June 2016. The descriptors used were: “nursing care”, “kidney disease”, “Fabry disease”, “Nursing care”. 42 articles were found. After the exclusion criteria, 16 articles were obtained as a final sample, grouped according to the author, year of publication, title, objective, type of study and results. The texts found were read, organized and synthesized in the thematic category: Nursing care for patients diagnosed with Fabry disease. Through the analysis of the studies it was possible to verify that Fabry's disease is complex and demands specific treatment, with nurses being an active and important professional in this aspect.